The progress of processing - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Assessment of the small-scale food processing subsector in Tanzania and Uganda Study report By H M Dietz, S Matee & W Ssali, CTA, 2000. 76 pp. ISBN 92 9081 232X Type of publication: study report CTA number 1020. 5 credit points